Pengaruh Ketersediaan Produk, Harga, dan Lokasi Terhadap Keputusan Pembelian Sepeda Motor HONDA di Dealer PT. Astra Motor - Ade Fitratul Akbar; Muhajirin Muhajirin; Juwani Juwani (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to determine the influence of product availability, price and location on the decision to purchase a HONDA motorbike at the PT Astra Motor dealer. The sample that will be used in this research is determined using the Ferninand formula (2014), namely sample = number of indicators x 5 to 10 because in this study there are 17 indicators, the number of samples used is a minimum sample of 17 x 5 = 85 respondents. Data analysis techniques use validity tests, reliability tests, classical assumption tests, multiple linear regression T tests and f tests. The results of this research state that: (1) Product availability has a partially significant effect on the decision to purchase a Honda motorbike at the PT dealer. Astra Motor Bima City. (2) Price has a partially significant effect on the decision to purchase a Honda motorbike at the PT dealer. Astra Motor Bima City. (3) Location does not have a partially significant effect on the decision to purchase a Honda motorbike at the PT dealer. Astra Motor Bima City. (4) Product Availability, Price and Location have a significant simultaneous influence on the Decision to Purchase a Honda Motorbike at the PT Dealer. Astra Motor Bima City.